Report of the Indian Tariff Board on the Heavy Chemical Industry - Government of India Central Publication Branch (Government of India Central Publication Branch, 1929)
The 1929 Indian Tariff Board Report on the Heavy Chemical Industry evaluates the current state and future prospects of India’s chemical sector, emphasizing chemicals such as sulphuric acid, nitric acid, hydrochloric acid, and related salts. The report highlights the industry’s strategic importance for agriculture, defense, and industrial growth, identifying challenges like high production costs, small-scale operations, and transport inefficiencies. Recommendations include protective tariffs, financial incentives, establishment of large-scale production units near raw material sources, and improvements in railway freight rates to reduce operational costs. Additionally, the report underscores the role of fertilizers in enhancing agricultural productivity, citing empirical data on nitrogen and phosphatic compounds. Overall, the report advocates coordinated industrial, fiscal, and infrastructural measures to develop a self-reliant, cost-effective chemical industry critical for India’s economic and national security.
Calcutta : Government of India Central Publication Branch 1929
Calcutta : Government of India Central Publication Branch
Keywords: Heavy Chemical Industry; Sulphuric Acid; Protective Tariffs; Fertilizers; Railway Freight; Economies of Scale; Nitrogen Compounds; Agricultural Productivity; Raw Material Availability; Industrial Policy